Effect of Airborne Pathogen Transmission Released by an Assailant in A Mosque Using CFD Simulation - Mat, Mohamad Nur Hidayat; Azman, Muhammad Faizal; M. Yusup, Eliza (International Journal of Integrated Engineering, 2023)
This study investigated the aerosol particle spreading characteristic under transient state at different location released by an assailant and determine the virus reproductive number over time at different location of virus released by an assailant. The spreading during coughing process will be validated with previous literature review using Computational Fluid Dynamics (CFD) simulation study. Mesh sensitivity study was done on the model to get better accuracy results and optimum computational load for the CFD simulation. The model involved in this study is the mosque and the prayers during the congregation prayers. The particle spreading characteristics are found to be influenced by the velocity distribution and velocity vector inside the mosque which is due to fan and air conditioner. Particles less than 10 µm are mostly deposited on the wall and ceiling and particles greater than 30 µm deposited on the ground or the prayers body. The location of assailant at the center are found to cause the most infection among the prayers which is 52% of the total prayer with the virus reproductive number (Ro) of 0.83. The assailant at top right and bottom right also produced high Ro of 0.73 and 0.6 while top left produced the lowest which is 0.32. The existence of partition is found to reduce the particle spreading from the assailant at bottom left.